Interactions of two novel stabilizing amendments with sunflower plants grown in a contaminated soil - Michálková, Zuzana; Martínez-Fernández, Domingo; Komárek, Michael (Chemosphere, 2017)
Several efficient stabilizing amendments have been recently proposed for the remediation of metal(loid)-contaminated soils. However, information on their interactions with plants, which is a crucial factor in soil environments, are still scarce. An amorphous manganese oxide (AMO) synthesized from organic compounds and nano zerovalent iron (nZVI) have been previously tested as promising stabilizing agents usable both for the stabilization of metals and As. Experiments with rhizoboxes were performed in order to evaluate their influence on the mobility of metal(loid)s in the bulk soil and rhizosphere of sunflower (Helianthus annuus L.) together with their impact on metal uptake and biomass yield. Generally, AMO proved more efficient than nZVI in all stages of experiment. Furthermore, the AMO effectively reduced water- and 0.01 M CaCl2-extractable fractions of Cd, Pb and Zn. The decreased bioavailability of contaminating metal(loid)s resulted in significant increase of microbial activity in AMO-amended soil. Together with metal(loid) extractability, the AMO was also able to significantly reduce the uptake of metals and ameliorate plant growth, especially in the case of Zn, since this metal was taken up in excessive amounts from the control soil causing strong phytotoxicity and even death of young seedlings. On the other hand, AMO application lead to significant release of Mn that was readily taken up by plants. Resulting Mn concentrations in biomass exceeded toxicity thresholds while plants were showing emergent Mn phytotoxicity symptoms. We highlight the need of such complex studies involving plants and soil biota when evaluating the efficiency of stabilizing amendments in contaminated soils.
Keywords: železo; Metals, Heavy; Stabilization; Immobilization; Iron; Oxides; Helianthus; Rhizobox; Soil Pollutants; látky znečišťující půdu; Nano zerovalent iron; půda; Manganese Compounds; Manganese oxide; biomasa; Environmental Restoration and Remediation; těžké kovy; oxidy; regenerace a remediace životního prostředí; Bacteria; Soil; Biomass; sloučeniny manganu